Beta-lactam and Fluoroquinolone Resistant Extraintestinal Escherichia coli from Broiler Chickens and Ducks: Public Health Threat - Abo Hashem, M; El-Mahallawy, HS; Moursi, M; Abd El-Fattah, R; Enany, M (Journal of the Hellenic Veterinary Medical Society, 2023)
Escherichia coli (E. coli) is a zoonotic bacterial pathogen commonly found in human, birds and animals. The widespread use of broad-spectrum beta-lactams for poultry treatment, has resulted in the production of extended spectrum β-lactamases (ESBLs) in E. coli. In this study, we analyzed the antimicrobial resistance pattern of E. coli isolates from broiler chickens and ducks with clinical colibacillosis, and investigated the presence of beta-lactam (blaTEM, blaSHV, ampC, and blaCTX-M) and fluoroquinolone (qnrS and qepA) resistance genes using PCR. E. coli isolates showed a higher resistance against beta-lactams: penicillin G and ceftriaxone (97.5%), cephalexin (92.5%), ampicillin (77.5%), amoxicillin/clavulanic acid (62.5%), with somewhat lower resistance for nalidixic acid (45%), ciprofloxacin (35%), and norfloxacin (32.5%) from fluoroquinolone group. Isolates showed considerable sensitivity to cefotaxime (65%) and levofloxacin (55%). All tested isolates carried blaTEM, blaSHV and ampC resistance genes, and this was associated with the phenotypic resistance too. Although some isolates showed phenotypic intermediate resistance to fluoroquinolones, or resistance to only one agent from this class, the qnrS (83.3%) has been detected with high frequency. The blaCTX-M (27.87%) and qepA (16.7%) showed the lowest occurrence and had been detected in isolates from broiler chickens only. The occurrence of these resistant E. coli serotypes in broiler chickens and ducks pose a potential threat to poultry industry, and constitutes a public health risk to human consumers, slaughterhouse and poultry packing plant workers due to dissemination of beta-lactam and fluoroquinolone resistant E. coli serotypes.